Tackling fraud and corruption in the United Nations - PORTELA, Clara (Institutional Knowledge at Singapore Management University, 2016)
It is June 2002 and Dileep Nair, Head of the Office of Internal Oversight Services (OIOS) at the UN headquarters in New York City, is responsible for fighting fraud and corruption within the UN. Nair is keenly aware that he needs additional staff and funding if he is to achieve any degree of success on behalf of OIOS. He is also aware that increasing the budget and headcount would be a battle in and of itself. So far Nair has been unsuccessful in convincing the budget approval committee to grant him more staff or funding. He now contemplates his next move. Following the reading of the case study and class discussion on it, students will gain a better understanding of UN policy. Students will also have the opportunity to develop a communication strategy, conduct a stakeholder analysis and calculate a budget.